EMERGING TRENDS IN RISK MANAGEMENT FOR EPC (ENGINEERING, PROCUREMENT, CONSTRUCTION) PROJECTS - Thompson, Helen; Davis, Richard (International Journal of Contemporary Research in Marketing and Management Sciences, 2024)
China's EPC (Engineering, Procurement, and Construction) industry has undergone significant growth, particularly driven by the "One Belt, One Road" initiative. Data reveals that Chinese EPC enterprises are capitalizing on the opportunities presented by this strategy. As of the latest statistics, Chinese firms account for a substantial 26% of the world's top 250 EPC companies. The Ministry of Commerce reports that Chinese enterprises have substantially expanded their footprint in foreign contracted projects related to the "Belt and Road," with a significant increase in newly signed contract values, indicating robust growth. As China enters the "14th Five-Year Plan" in 2021, the state's emphasis on general contracting has risen, necessitating higher standards for construction companies to operate across the entire industry chain.